Fractures of the pelvis and acetabulum - Tile, Marvin; Helfet, David; Helfet, David; Tile, Marvin (AO Foundation, 2015)
The fourth edition of this well-known and highly regarded book by Marvin Tile et al. is now a two-volume set of books based on the AO principles of operative management of fractures, as applied to the pelvis and acetabulum. With the collaboration of over 80 international expert surgeons and through hundreds of images and illustrations, each volume emphasizes decision making based on the assessment of the personality of the injury through the patient's history, physical examination, and interpretation of radiographic investigations. Access to video presentations demonstrating surgical approaches and reduction techniques performed by world-renowned experts is included